P149 Haematopoietic stem cell transplantation in systemic sclerosis: Sheffield Teaching Hospitals' experience. (20th April 2020) - Smith, Ruth; Snowden, John; Akil, Mohammed
Abstract: Background: Haematopoietic stem cell transplantation (HSCT) was first used as a treatment for systemic sclerosis (SSc) in the 1990s. By April 2018 the European Society for Blood and Bone Marrow Transplantation had 533 cases on its registry. Sheffield is the main UK centre for HSCT for SSc with 6 people having undergone the procedure since 2007. HSCT works by rebooting the immune system. Autoreactive T cells are suppressed by proliferation of regulatory T cells and improvement in T cell receptor diversity. Autologous HSCT has been shown to be an effective treatment for SSc, and has been compared to monthly pulsed intravenous cyclophosphamide in the ASSIST, ASTIS and SCOT trials. HSCT showed greater improvement in respiratory and cutaneous disease (ASSIST) and produced a superior global rank composite score based on a hierarchy of disease features (SCOT) compared with cyclophosphamide. However, although there was longer term survival benefit compared with cyclophosphamide, treatment related mortality (TRM) was high at 10% (ASTIS). TRM was attributed to SSc-related cardio-pulmonary dysfunction, and therefore patient selection for HSCT is important and all must undergo a thorough cardio-pulmonary evaluation to mitigate risk. Methods: We performed a retrospective review of the characteristics and outcomes of patients who have undergone HSCT for SSc in Sheffield. Results: Legend Symptom s: R Raynaud's; DU digital ulcers; dSSc diffuse systemic sclerosis; ILD interstitial lung disease; P pericarditis; M myositis; GAVE gastric antral vascular ectasia; SRC scleroderma renal crisis. Previous treatments: MTX methotrexate; MMF mycophenolate; CYA cyclosporine; CYCLO cyclophosphamide; AZA azathioprine; HCQ hydroxychloroquine mRSS modified Rodnan skin score Conclusion: Patient numbers are small and follow-up is limited to 12 years, but the procedure has been well tolerated and improved patients' skin score, with the exception of patient 6. His pre-procedure screening tests showed no evidence of interstitial lung disease, pulmonary artery hypertension or left ventricular dysfunction. The cause of his acute deterioration is unclear but acute campylobacter myocarditis or cyclophosphamide cardiac toxicity have been postulated. Sheffield's experience has shown HSCT to be an effective treatment for SSc, but one that is not without risk. Disclosures: R. Smith None. J. Snowden Other; Speaker fees at educational events supported by Janssen, Jazz, Mallinckrodt & Gilead. Member of a trial IDMC for Kiadis Pharma. Chairs NHS England Clinical Reference Group for Blood & Marrow Transplan. M. Akil Honoraria; AbbVie, Actelion, Celgene, Astra Zenica, Lilly and UCB.